Approach to the Types of State Based on Russian Jurist Perspective - Hop, Nguyen Canh (VNU Journal of Science: Legal Studies, 2020)
Types of state and typology of states is always one of the major subjects of theory of state and law. The Marxist - Leninist theory of socio-economic forms and theory of civilization are two theories when studying this topic. Each way of approaching has great values as well as certain limitations. Therefore, it is important to look for their rational points to understand the nature and role of the state fairly, being suitable to its development history and diversity. This article summarizes views of Russian jurists on the above issue. Keywords: Types of state, theory of socio-economic forms, theory of civilization, views of Russian jurists. References: [1] M.N. Marchenco, Theory of state and law, Iuridicheskaia Literatura Publishing House, Matxcova (1996) 90-96. [2] V.N. Khropanhiuc, Theory of state and law, Ochiechestvo Publishing House Matxcova, (1993) 63-72. [3] V.V. Lazarev, Theory of state and law, Iurist, Matxcova (1995) 243-247. [4] V.N. Khropanhiuk, Lí luận nhà nước và pháp luật, Ochiechestvo Publishing House, Matxcova (1993) 68-70. [5] M.N. Marchenco, (Chủ biên), Lí luận nhà nước và pháp luật, Norma Publishing House, Matxcova, 1 (2010) 199-227. [6] A.I. Đemiđop, Practical methodology in jurisprudence, Journal of Jurisprudence, No.4 (2001)14. [7] V.V. Ilin, Politics, Knhigee Publishing House Universitet, Matxcova, (1999) 79. [8] T.N. Ratko, V.V. Lazarev, L.A. Morosova, Theory of state and law, Prospect Publishing House, Matxcov (2015) 454-458. [9] Ho Chi Minh, Complete Works, National Political Publishing House, Hanoi (1995) 465. [10] D.L Brandenberger, A brief synopsis of "History of the Russian Bolshevik Communist Party of", ("Ensin B.N. Presidential Research Center", Moscow, Russian, 2014. [11] A.V. Vengerov, Theory of state and law, part 1. Theory of state, Iurisprudensia Publishing House, Moscow, (2000) 87. [12] Iu.V. Laptov, Eastern Despotism, Journal of Economic-Historical Research Moscow, Russian (2007). [13] C. Marx and Ph., Complete Works, Political Publishing House (Polichicheskaia Literatura), Moscow, Russian, Vol. 22, (1975) 200-201. [14] V.I.Lê-nin, Toàn tập, Tập 39, NXB Tiến bộ Progres, Мatxcova (1977) 73. [15] V.I.Lenin Complete Works, Progressive Publishing House (Progres), Moscow, Russian, Vol. 39 (1977) 73. [16] R.Z. Livshis, Nhà nước và pháp luật trong xã hội ngày nay: sự cần thiết có cách tiếp cận mới, Tap chí Nhà nước và pháp luật Xô viết, số 10 (1990) 14. [17] A.Ia. Gurevich, Lí thuyết hình thái và thực tiễn lịch sử. Tạp chí Những vấn đề triết học, số 11 (1990). [18] M. Barg, Cách tiếp cận theo các nền văn minh về lịch sử. Tạp chí Komunist, số 3 (1991) 29. [19] A.I Gurevich: Triết học và sử học, Tạp chí Những vấn đề triết học, Matxcova, số 10 (1988), 20. [20] O.A Rogacheva, О. А. Рогачева, Основные подходы к типологии государства) // Концепт. - 2014. - Спецвыпуск № 24. -ART 14791. - 0,4 п. л. - URL: http://e-kon- cept.ru/2014/14791.htm. - Гос. рег. Эл № ФС 7749965. - ISSN 2304-120X. ART 14791 УДК 340.15 (Truy cập ngày 14/02/2020). [21] A.Ph. Vishnhievski và Iu.A. Meliekholies, Проблемы типологии государства и права в современной теоретической юридической науке. А. Ф. Вишневский , Ю. А. Мелеховец, https://www.barsu.by/vestnik/Download/hist_6_2018_114.pdf, truy cập 14/02/2020). [22] Hoàng Thị Kim Quế, Giáo trình Lí luận nhà nước và pháp luật, NXB Đại học Quốc gia Hà Nội, (2015) 107.